Vogue on Hubert de Givenchy - Beyfus, Drusilla (Abrams Image, 2015)
The fashion aesthetic of handsome, aristocratic Hubert de Givenchy combined the traditions of haute couture--creative, luxurious, and perfectionist--with a modern entrepreneurial sensibility. In a career spanning 40 years, he created the most glamorous of evening dresses, developed the influential "sack" dress, and produced debonair daytime suits that have never gone out of fashion. He also famously defined the sartorial image of Audrey Hepburn--both onscreen and off--designing the little black dress for Breakfast at Tiffany's. Created by the editors of British Vogue, Vogue on Hubert de Givenchy features biography and history studded with more than 80 images from their unique archive of images taken by leading photographers such as Irving Penn, Patrick Demarchelier, and Cecil Beaton.